2019
DOI: 10.21608/ejchem.2019.18333.2127
|View full text |Cite
|
Sign up to set email alerts
|

Features of Rooting Paulownia in Vitro

Abstract: T HE presented materials deal with the topical problem of rhizogenesis induction and rooting of genus paulownia plants obtained by in vitro method. According to the research results, the optimal composition of the nutrient medium for the regenerants cultivation on the stage of rhizogenesis induction has been defined, the technologically optimal age of the regenerants for the in vitro -ex vitro transition, the depth of the seedlings, the number of post-septic nipples has been established. The obtained results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
(2 reference statements)
1
2
0
4
Order By: Relevance
“…Вважають, що найбільш активна детермінація екзогенної природи властива першим етапам процесу розвитку (Filipova et al, 2019). Подальший вплив детермінант відбувається на фоні зкоородинованих внутрішніх механізмів (Terek & Patsula, 2011).…”
Section: вісник сумського національного аграрного університетуunclassified
“…Вважають, що найбільш активна детермінація екзогенної природи властива першим етапам процесу розвитку (Filipova et al, 2019). Подальший вплив детермінант відбувається на фоні зкоородинованих внутрішніх механізмів (Terek & Patsula, 2011).…”
Section: вісник сумського національного аграрного університетуunclassified
“…Таку властивість дерева вигідно використовують лісозаготівельні господарства та деревообробні підприємства, так як це суттєво знижує витрати на посадку дерева з нуля та догляд за ним. Приріст деревини становить 1 м 3 за 7-8 років [2].…”
Section: виклад основного матеріалуunclassified
“…The most effective method of vegetative propagation is clonal micropropagation in vitro, which provides a high reproduction rate, genetic identity of the source material and recovery of plants from pathogens. Some aspects of clonal micropropagation of Paulownia have been studied in [4][5][6][7][8][9][10][11], but it is necessary to optimize some techniques in connection with the influence of genotype and level of processability. No scientific publications have been identified on the cultivation of Paulownia in the Southern Steppe of Ukraine, so research on the adaptive capacity of the plant in specific climatic and environmental conditions is relevant.…”
mentioning
confidence: 99%
“…After 7-20 days, material was taken from the shoots for further work [4]. A similar approach was used in the studies presented in works [2,[5][6][7], but it was noted that the optimal period for the selection of plant material is December-January, but it is also possible to select in August-October, while the buds must be treated with gibberellic acid to wake up. According to the results of research [8], it is shown that the best for the height of regenerants and the number of microshoots in the conglomerate is a weakly acidic environment with a pH of 5.6-5.8.…”
mentioning
confidence: 99%